2017
DOI: 10.5376/ijms.2017.07.0021
|View full text |Cite
|
Sign up to set email alerts
|

Otolith Mass Asymmetry in Two Parrotfish Species, <i>Chlorurus sordidus</i> (Forsskal, 1775) and <i>Hipposcarus harid</i> (Forsskal, 1775) from Hurghada, Red Sea Coast of Egypt

Abstract: The asymmetry in the mass of the sagitta of the parrotfish species, Chlorurus sordidus and Hipposcarus harid collected from Hurghada, Red Sea coast of Egypt was investigated. In the present study, the weight of the difference between the weight of the sagitta from both the left and right sides was divided by average otolith mass. The results shown that the value of x in the two-species studied does not related to the length of the fish, though the value of otolith weight difference has shown a trend of increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
4
7
0
Order By: Relevance
“…The results acquired in the present study of the saccular otolith mass asymmetry in S. melanotheron and C. guineensis show that it does not depend on the fish size. This agrees with the results gained by other researchers on several marine and freshwater fish species (Lychakov & Rebane 2004, 2005, Lychakov et al 2006, Jawad 2013, Jawad & Sadighzadeh 2013, Jawad et al 2011, 2012a, 2012b. However, the relationship between otolith mass difference and fish length is more complex.…”
Section: Discussionsupporting
confidence: 92%
“…The results acquired in the present study of the saccular otolith mass asymmetry in S. melanotheron and C. guineensis show that it does not depend on the fish size. This agrees with the results gained by other researchers on several marine and freshwater fish species (Lychakov & Rebane 2004, 2005, Lychakov et al 2006, Jawad 2013, Jawad & Sadighzadeh 2013, Jawad et al 2011, 2012a, 2012b. However, the relationship between otolith mass difference and fish length is more complex.…”
Section: Discussionsupporting
confidence: 92%
“…This study showed results support those acquired for a number of fish species, where otolith mass non-asymmetry dissociate with the fish length (Jawad et al, 2017). Nevertheless, the relationship of the otolith mass difference and fish size is complicated.…”
Section: Discussionsupporting
confidence: 76%
“…During the last decades, study of the morphological characteristics of otoliths, in particular their shape, length, width, area, thickness and weight, has been used to test both genetic and environmental stressors and as a bioindicator to test the differentiation of populations and the variance in stock discrimination studies using Elliptical Fourier analysis (EFA) (Valentine et al, 1973;Campana & Casselman, 1993;Begg & Waldman, 1999;Torres et al, 2000;Smith et al, 2002;Panfili et al, 2005;Turan, 2006;Jawad et al, 2010Jawad et al, , 2011Jawad et al, , 2012aJawad et al, , 2012bJawad et al, , 2012cJawad et al, , 2016Jawad et al, , 2020Vignon & Morat, 2010;Cañás et al, 2012;Jawad, 2012Jawad, , 2013Lord et al, 2012;Treinen-Crespo et al, 2012;Mahe et al, 2014;Trojette et al, 2014Trojette et al, , 2015Abu El-Regal et al, 2016;Brophy et al, 2016;Hüssy et al, 2016;Rebaya et al, 2016Rebaya et al, , 2017Al-Busaidi et al, 2017;Fatnassi et al, 2017;Ider et al, 2017;Khedher et al, 2017;Rodgveller et al, 2017;Chakour & Elouizgani, 2018;Khemiri et al, 2018;Kontaş et al, 2018;Mejri et al, 2018;Wang et al, 2018;…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, study of the morphological characteristics of otoliths, in particular their shape, length, width, area, thickness and weight, has been used to test both genetic and environmental stressors and as a bioindicator to test the differentiation of populations and the variance in stock discrimination studies using Elliptical Fourier analysis (EFA) (Valentine et al ., 1973; Campana & Casselman, 1993; Begg & Waldman, 1999; Torres et al ., 2000; Smith et al ., 2002; Panfili et al ., 2005; Turan, 2006; Jawad et al ., 2010, 2011, 2012 a , 2012 b , 2012 c , 2016, 2020; Vignon & Morat, 2010; Cañás et al ., 2012; Jawad, 2012, 2013; Lord et al ., 2012; Treinen-Crespo et al ., 2012; Mahe et al ., 2014; Trojette et al ., 2014, 2015; Abu El-Regal et al ., 2016; Brophy et al ., 2016; Hüssy et al ., 2016; Rebaya et al ., 2016, 2017; Al-Busaidi et al ., 2017; Fatnassi et al ., 2017; Ider et al ., 2017; Khedher et al ., 2017; Rodgveller et al ., 2017; Chakour & Elouizgani, 2018; Khemiri et al ., 2018; Kontaş et al ., 2018; Mejri et al ., 2018; 2020; Wang et al ., 2018; Ben Mohamed et al ., 2019; Fashandi et al ., 2019; Jmil et al ., 2019; Mahé et al ., 2019; Puentes et al ., 2019; Osman et al ., 2020). Indeed, these studies have shown that the otolith shape is species-specific (Sadighzadeh et al ., 2014) and that variability in the otolith shape, structure and development is influenced by ontogenetic, genetic and environmental factors (Campana & Casselman, 1993; Cardinale et al ., 2004; Vignon & Morat, 2010; Vignon, 2015; Hüssy et al ., 2016; Ider et al ., 2017; Fashandi et al ., 2019), as well as by sex, growth, maturity and pattern of fishery exploitation (Begg & Brown, 2000), or by individual characteristics, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation